Microcontroller-based three-phase inverter and rectifier-buck DC/DC converter - Setya Tutuko, Widya Ageng (2014)
Efficient and stable power electronic devices are critical components in order to increase energy efficiency which at the eventual will reduce carbon emission. As one of intermediary power electronic devices, power converter is now becoming a subject for rapid development to support the idea of emission reduction. This project is to develop microcontroller-based three-phase inverter and rectifier that can be functioning as the interface between battery, three-phase load, and utility grid.